2013
DOI: 10.3892/br.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphism of HLA-DRB1 antigens with the susceptibility to lepromatous leprosy

Abstract: Abstract. Despite the introduction of multidrug therapy and the overall reduction of leprosy prevalence in Mexico, the disease remains endemic in certain regions of the country. A genetic basis for the immune susceptibility to Mycobacterium leprae has already been established in different populations worldwide. In this study, we investigated the possible association of the HLA-DRB1 alleles with leprosy in a Mexican Mestizo population. The results demonstrated that the HLA-DRB1*01 allele is associated with lepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For this purpose and taking into account that the majority of cases of leprosy in Mexico are MB [3, 15], we only considered the MB leprosy and control group for this analysis. The distribution of genotypic and allelic frequencies of IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene polymorphisms in patients with leprosy and healthy controls is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose and taking into account that the majority of cases of leprosy in Mexico are MB [3, 15], we only considered the MB leprosy and control group for this analysis. The distribution of genotypic and allelic frequencies of IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene polymorphisms in patients with leprosy and healthy controls is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the possible association with leprosy in 144 Mexican Mestizo individuals (75 leprosy patients and 69 healthy controls) who were genotyped for the IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene polymorphisms. For this purpose and taking into account that the majority of cases of leprosy in Mexico are MB [ 3 , 15 ], we only considered the MB leprosy and control group for this analysis. The distribution of genotypic and allelic frequencies of IL-17A G-197A (rs227593) and IL-17F A7488G (His161Arg, rs763780) gene polymorphisms in patients with leprosy and healthy controls is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although leprosy is of infectious etiology, studies have demonstrated that a genetic component and its variability serve a crucial role in the establishment and progression of the disease (5,6). In previous reports, our group observed that human leukocyte antigen (HLA)-DRB1*01 and HLA-A*28 alleles were associated with susceptibility to leprosy, whereas HLA-DRB1*08 was associated with resistance, in a Mexican mestizo population (23,24). The rs2476601 polymorphism of PTPN22 has been associated with a negative regulatory function in T-cell signaling and with autoimmune diseases including type 1 diabetes (25), rheumatoid arthritis (26) and systemic lupus erythematosus (27), and several infectious diseases including tuberculosis and leprosy (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 90%
“…() studied 92 patients and 315 controls from a Mexican‐American population, showing no significant differences for HLA‐A and ‐B serotypes among the groups. Recently, our group reported that HLA‐DRB1*01 is associated with susceptibility to LL and DL in a study performed with 52 patients and 99 controls from seven states of Mexico (Mónica Escamilla‐Tilch, ). Altogether, these results suggest that involvement of HLA antigens in susceptibility to leprosy in Mestizos may be influenced by the genetic diversity found in different resident populations of Mexico (Moreno‐Estrada et al., ).…”
Section: Discussionmentioning
confidence: 99%